67 THE USE OF COMPUTED TOMOGRAPHIC CORONARY ANGIOGRAPHY IN THE ASSESSMENT OF PLAQUE TYPE AND ITS RELATIONSHIP TO DEGREE OF STENOSIS AND GENDER. Issue 1 (1st January 2007) - Gottsegen, J.; Prakash, M.; Lubarsky, L.; Coplan, N.; Hecht, H.
Abstract : Background: The Glagov hypothesis suggests that positive remodeling preserves lumen size until further plaque formation results in significant narrowing. However, there are no data relating the percent stenosis (%S) to the plaque type and its relationship to patient's gender. Methods: Fifty patients undergoing 64-detector computed tomographic angiography (CTA) were evaluated using the AHA 18 segment model. Stenoses were assigned to quartiles: 0 to 25%, 25 to 50%, 50 to 75%, and > 75%. Plaque was characterized as totally noncalcified (TNC), predominantly nonC (PNC), predominantly C (PC), and totally C (TC). Results: There was a significant ( p < .01) direct relationship between the extent of noncalcified plaque and the %S. The association was statistically significant for women but not for men ( p < .01 and p = .2, respectively; Table ). Conclusions: (1) There is a significant association between vessel lumen and calcification in females but not in males. (2) Noncalcified plaque is directly, and calcified plaque inversely, related to the severity of arterial narrowing; this suggests that positive remodeling associated with predominantly calcified plaque preserves lumen size.